Lactoferrin/sialic acid prevents adverse effects of intrauterine growth restriction on neurite length: investigations in an in vitro rabbit neurosphere model - Kühne, Britta Anna; Gutierrez-Vázquez, Lara; Sánchez Lamelas, Estela; Guardia-Escote, Laia; Pla, Laura; Loreiro, Carla; Gratacós, Eduard; Barenys, Marta; Illa, Miriam (Frontiers in Cellular Neuroscience, 2023)
Introduction Intrauterine growth restriction (IUGR) is a well-known cause of impaired neurodevelopment during life. In this study, we aimed to characterize alterations in neuronal development underlying IUGR and discover strategies to ameliorate adverse neurodevelopment effects by using a recently established rabbit in vitro neurosphere culture. Methods IUGR was surgically induced in pregnant rabbits by ligation of placental vessels in one uterine horn, while the contralateral horn remained unaffected for normal growth (control). At this time point, rabbits were randomly assigned to receive either no treatment, docosahexaenoic acid (DHA), melatonin (MEL), or lactoferrin (LF) until c-section. Neurospheres consisting of neural progenitor cells were obtained from control and IUGR pup’s whole brain and comparatively analyzed for the ability to differentiate into neurons, extend neurite length, and form dendritic branching or pre-synapses. We established for the very first time a protocol to cultivate control and IUGR rabbit neurospheres not only for 5 days but under long-term conditions up to 14 days under differentiation conditions. Additionally, an in vitro evaluation of these therapies was evaluated by exposing neurospheres from non-treated rabbits to DHA, MEL, and SA (sialic acid, which is the major lactoferrin compound) and by assessing the ability to differentiate neurons, extend neurite length, and form dendritic branching or pre-synapses. Results We revealed that IUGR significantly increased the neurite length after 5 days of cultivation in vitro, a result in good agreement with previous in vivo findings in IUGR rabbits presenting more complex dendritic arborization of neurons in the frontal cortex. MEL, DHA, and SA decreased the IUGR-induced length of primary dendrites in vitro, however, only SA was able to reduce the total neurite length to control level in IUGR neurospheres. After prenatal in vivo administration of SAs parent compound LF with subsequent evaluation in vitro, LF was able to prevent abnormal neurite extension. Discussion We established for the first time the maintenance of the rabbit neurosphere culture for 14 days under differentiation conditions with increasing complexity of neuronal length and branching up to pre-synaptic formation. From the therapies tested, LF or its major compound, SA, prevents abnormal neurite extension and was therefore identified as the most promising therapy against IUGR-induced changes in neuronal development.